2013
DOI: 10.1177/0887302x13506111
|View full text |Cite
|
Sign up to set email alerts
|

Age, Body Size, Body Image, and Fit Preferences of Male Consumers

Abstract: This study examines the influence of specific physical factors (body size), demographic factors (age), and psychosocial factors (body satisfaction, social physique anxiety, and drive for muscularity) on apparel-specific (jeans, khakis, dress shirts, and polo shirts) fit preferences of male consumers. Data were collected through an online survey administered to 141 men in the age group of 19-66 years. Results revealed that increase in body size significantly predicted preferences for apparel (jeans, dress, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 36 publications
1
65
0
Order By: Relevance
“…Men also preferred higher waist lines for jeans as their BMI increased. The results of Sindicich and Black (2011) and Chattaraman et al (2013) suggested that it is important to study the relationship between men's BMI and fit preferences in the outdoor performance category to see if similar results are found. Hence, the following research question was proposed:…”
Section: Fit Preferences and Bmisupporting
confidence: 72%
See 4 more Smart Citations
“…Men also preferred higher waist lines for jeans as their BMI increased. The results of Sindicich and Black (2011) and Chattaraman et al (2013) suggested that it is important to study the relationship between men's BMI and fit preferences in the outdoor performance category to see if similar results are found. Hence, the following research question was proposed:…”
Section: Fit Preferences and Bmisupporting
confidence: 72%
“…In the present study, the overweight BMI group discussed this issue more than the normal BMI group. Similarly, Chattaraman et al (2013) found that larger men (who had higher BMI's) preferred looser fitting jeans. In order to prevent possible hip and seat tightness, two possible solutions are to (1) insert stretch material at the side seams of the pants and to (2) improve the grading by adding slightly more room at the hip circumference for larger sizes.…”
Section: Fit Preferences Influenced By Bmimentioning
confidence: 94%
See 3 more Smart Citations